Laboratory Utilization Review as a Trigger for Hospital Quality Improvement - Zahra Meidani; Mehrdad Farzandipour; Alireza Farokhian; Masome Haghighat; Zahra Nazemi Bidgoli (Tehran University of Medical Sciences, 2017)
Background and Aim: In attention to pressing need to cost containment and service efficiency, laboratory services serve as a central locus for controlling health care expenditure. This study intents to investigate proportion of laboratory utilization in Iran to pave the way for future interventions. Materials and Methods: A cross-sectional study was conducted to investigate the proportion for laboratory utilization through the retrospective analysis of 384 medical records at the tertiary care Kashan University Hospital Shahid Beheshti. To pave the way for future intervention, over utilization tests were classified into two categories, inappropriate and resulted in laboratory errors. Results: Nine thousand five hundred forty one laboratory tests were ordered, 2522 (26.40%) of the tests were inappropriate and 143 (1.5%) of the over utilization tests have occurred due to laboratory testing cycle errors. According to reviewers' judegment relevancy to medical intervention was considered as the most accepted appropriateness criteria 5012 (52.53%) for laboratory tests  Conclusion: Since, the laboratory tests over utilization is multifactorial, forming a multidisciplinary team including physicians, nurses, laboratory staff, medical education experts, health care management and health information technology staffs in terms of Utilization Committee to develop more targeted strategy based on root cause analysis of over utilization behavior seems necessary.